2023
DOI: 10.1029/2022jf006967
|View full text |Cite
|
Sign up to set email alerts
|

Transient Response and Adjustment Timescales of Channel Width and Angle of Valley‐Side Slopes to Accelerated Incision

Abstract: Studying bedrock rivers during their transient states helps understand the response of a fluvial system to the changing boundary conditions. Although theoretical studies predict how river form adjusts to changes in incision or rock uplift rates, field constraints on the timescale of this adjustment are limited. We investigated the transient behavior of channels and hillslopes and estimated the adjustment times of channel width and angle of valley‐side slopes to accelerated incision based on knickpoint travel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…In the contrast, the adjustment of fluvial channel profile to tectonic uplift, where the spatial patterns of erosion and sediment transport are gradually reshaped from the downstream to the upstream areas, usually lasts more than millions of years (Glotzbach, 2015; Goren et al, 2022). Current studies have demonstrated that channel profiles continue to steepen with increases in erosion rates far beyond (at least three to five times higher than) the rate value where threshold hillslopes emerge (Hilley et al, 2019; Kirby et al, 2010; Ouimet et al, 2009; Takahashi et al, 2023). Thus, the speed and degree of channel response to tectonic uplift exert a first‐order control on the timescales for which landscape reaches an uplift–erosion balance state and on the topographic relief at the orogenic scale (Hilley et al, 2019; Kirby & Whipple, 2012; Whipple et al, 1999; Whipple & Tucker, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the contrast, the adjustment of fluvial channel profile to tectonic uplift, where the spatial patterns of erosion and sediment transport are gradually reshaped from the downstream to the upstream areas, usually lasts more than millions of years (Glotzbach, 2015; Goren et al, 2022). Current studies have demonstrated that channel profiles continue to steepen with increases in erosion rates far beyond (at least three to five times higher than) the rate value where threshold hillslopes emerge (Hilley et al, 2019; Kirby et al, 2010; Ouimet et al, 2009; Takahashi et al, 2023). Thus, the speed and degree of channel response to tectonic uplift exert a first‐order control on the timescales for which landscape reaches an uplift–erosion balance state and on the topographic relief at the orogenic scale (Hilley et al, 2019; Kirby & Whipple, 2012; Whipple et al, 1999; Whipple & Tucker, 2002).…”
Section: Introductionmentioning
confidence: 99%